Ja nie znałem żadnych piosenek. Męskie doświadczenie adopcji - Maciejewska-Mroczek, Ewa; Reimann, Maria (Uniwersytet Wrocławski. Wydział Nauk Społecznych. Instytut Socjologii, 2021)
This article concerns the men’s experience of becoming an adoptive father. Based on in-depth interviews conducted as part of the research project “Adoption as a Process, Experience, and Institution. Anthropological Perspective”, we describe how men think about creating a bond with the adopted child and what they consider to be the most important in becoming a parent. The interviewed men considered adoptive parenthood to be more difficult than biological parenthood and, therefore, felt insecure and frightened. In the article, we present strategies they used to overcome this insecurity: preparing well, finding support in the relationship with their wives, spending time with the child, and finding deeper meaning. Those strategies helped them think of the child as really “one’s own” and feel confident as a father. We also show how important a good, strong relationship with the wives was for our interviewees.
Keywords: adoption; fatherhood; parenthood; men; masculinity